BREAST MILK AS AN ALTERNATIVE FOR POSTPARTUM PERINEAL CARE - Yuli Admasari; Bedjo Santoso; Titi Suherni; Imam Djamaluddin Mashoedi; Mardiyono Mardiyono (Belitung Raya Foundation, Indonesia, 2017)
Background: Perineal laceration during childbirth is very common among mothers; however, some of them may suffer from its complication if not treated properly. Objective: To prove the effectiveness of breast milk as an alternative topical ingredient in the treatment of perineal wound in postpartum mothers. Methods: This was a quasi-experimental study with non-equivalent control group posttest only design. There were 30 respondents selected in this study, with 15 assigned in an intervention group and a control group. Accidental sampling was used to select the samples with the criteria that the respondents had perineal laceration in level 1 and 2. Data were analyzed using Mann Whitney test. Results: Effective wound healing process can be seen in the intervention group from 80% of poor category in 6-10 hours (1st period) of postpartum became 86.7% of good category in 7 days of postpartum (4th period). Different from the control group that showed the slow progress of wound healing, which was 86.7% of poor category in the 1st period to only 33.3% of good category in the 4th period. Mann Whitney test showed that there was a significant mean difference of the perineal wound healing process between the intervention group (11.23) and the control group (19.77) with p-value 0.002 (<0.05). Conclusion: Breast milk was more effective than povidone iodine in the treatment of perineal wound. It is suggested to health workers, especially midwife to apply this intervention to accelerate the healing of perineal wound in midwifery care.